The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0363546519875137
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Test Environment, Age, Sex, and Sport on Baseline Computerized Neurocognitive Test Performance

Abstract: Background: Baseline computerized testing is a common component of concussion assessments, and the testing environment has been suggested to influence test performance and validity. Purpose: To compare concussion baseline computerized neurocognitive test performance and validity among adolescent athletes based on testing environment (group, individual), age group (10-12, 13-15, 16-18 years), sex (male, female), and sport type (collision/combat, contact, noncontact). Study Design: Cohort study; Level of evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
(35 reference statements)
1
11
0
Order By: Relevance
“…Previous studies of adolescent12 and collegiate10 11 athletes found no association between sport and neurocognitive test performance and no significant differences for sport type on composite scores during baseline preseason evaluations. A similar large scale investigation of male NCAA athletes undergoing preseason testing found that football players had lower (worse) visual motor processing speed and slower (worse) reaction time compared with non-contact sport athletes, however, the authors reported small effect sizes and minimal clinical relevance, similar to our study 9.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Previous studies of adolescent12 and collegiate10 11 athletes found no association between sport and neurocognitive test performance and no significant differences for sport type on composite scores during baseline preseason evaluations. A similar large scale investigation of male NCAA athletes undergoing preseason testing found that football players had lower (worse) visual motor processing speed and slower (worse) reaction time compared with non-contact sport athletes, however, the authors reported small effect sizes and minimal clinical relevance, similar to our study 9.…”
Section: Discussionmentioning
confidence: 68%
“…Others have examined the influence of sport on cognition across an athletic season and found small but measurable short-term differences in neurocognitive outcomes between collision, contact and non-contact high school and collegiate athletes,13 although the magnitude of the differences between sport type did not reach the thresholds deemed to be clinically significant and did not persist across subsequent athletic seasons 13. Similarly, previous studies have found lower symptom scores in adolescent12 and collegiate athletes10 associated with collision sport participation. It is not known as to why collision sport athletes report fewer symptoms, but it is possibly due, at least in part, to collision sports being predominantly male, as sex has been associated with baseline symptom reporting in a number of studies 26 27 34.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Computer-based neurocognitive testing could be performed at an athlete’s home but administered or proctored using telehealth to ensure proper testing procedure. French et al found that although environment did not affect test performance, those who tested in an individual testing environment had, on average, a higher concussion symptom severity score than those who underwent testing in a group [11]. Other tests that may be used in baseline testing such as the Vestibular Ocular-Motor Screen would require another examiner to be physically present with the athlete [22].…”
Section: Discussionmentioning
confidence: 99%
“…All participants were separated into one of the six age groupings: ages 12 and under, 13-15, 16-19, 20-29, 30-39, and 40+. e younger age group clusters were chosen based on previous reports showing differences in concussion symptomology [25,26]. A total of 1,577 participants were included in the study for the experimental data (see Table 1 for number of participants per category).…”
Section: Methodsmentioning
confidence: 99%